Demoralization and well-being among self-employed individuals with cardiac disease: the role of intolerance of uncertainty - Sowan, Wafaa; Kissane, David (Frontiers in Psychology, 2024)
Background Individuals with cardiac disease (CD) who are self-employed may experience ability limitations and especially intensive challenges and uncertainties. These challenges may cause demoralization and impaired well-being. Objectives To examine: (a) whether work ability limitations are related to demoralization and well-being among self-employed people with CD; (b) rates of demoralization; and (c) how demoralization and intolerance of uncertainty (IU) are associated with well-being. Methods The study involved 120 self-employed individuals with CD. The PROCESS macro was used to analyze mediation and moderation processes. Results The prevalence of demoralization syndrome was 37.4%. Work ability-limitations were associated with higher demoralization levels. Demoralization was associated with well-being only among participants with high IU. Further, demoralization mediated the relationship between work ability limitations and well-being only for individuals with high IU. Conclusion Encountering limitations among self-employed was associated with demoralization and lower levels of well-being, especially among those with high IU. In addition, demoralization syndrome is prevalent among individuals with CD in general. Early recognition and treatment of demoralization as a treatable psychological syndrome are essential for preventing its degeneration into more complex forms. In addition to uncertainty related to health, it is important to pay special attention to other sources of uncertainty.